2009
DOI: 10.1590/s0102-33062009000300024
|View full text |Cite
|
Sign up to set email alerts
|

Flora da Paraíba, Brasil: Solanum L. (Solanaceae)

Abstract: Neste trabalho apresenta-se o tratamento taxonômico do gênero Solanum, como parte do projeto "Flora da Paraíba", que vem sendo realizado com o objetivo de identificar e catalogar as espécies da flora local. Realizaram-se coletas, observações de campo e estudos morfológicos para as identificações, descrições e ilustrações botânicas, com o auxílio da bibliografia especializada, complementadas pela análise de tipos e fotos de tipos de herbários nacionais e internacionais e de espécimes depositados nos herbários E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
0
9
0
9
Order By: Relevance
“…In Minas Gerais, this species is considered rare, with a few isolated records from low-and high-montane semi-deciduous seasonal forest (Oliveira-Filho, 2006). This species is also considered rare in the state of Paraíba, where it is associated to moist forests (Agra et al, 2009). Stehmann et al (2014) report the occurrence of the species in the states of Alagoas, Pernambuco and Sergipe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Minas Gerais, this species is considered rare, with a few isolated records from low-and high-montane semi-deciduous seasonal forest (Oliveira-Filho, 2006). This species is also considered rare in the state of Paraíba, where it is associated to moist forests (Agra et al, 2009). Stehmann et al (2014) report the occurrence of the species in the states of Alagoas, Pernambuco and Sergipe.…”
Section: Discussionmentioning
confidence: 99%
“…However, no records from these states were found in the databases or in the published literature. The species is a terricolous sciophilous treelet (Agra et al, 2009;Feliciano and Salimena, 2011) found in semi-deciduous seasonal forest (Stehmann et al, 2009), moist upland forest ("brejos de altitude", (Agra et al, 2009)), and shaded areas of coastal forests in the Atlantic forest domain (Feliciano & Salimena, 2011;Stehmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It comprises 2800-3000 species belonging to 85-90 genera of herbs, shrubs, and a few trees (Woodland, 1997); cosmopolitan, occurring around the world except in the Artic area. The major part of species is located in South America (Schultes & Raffauf, 1990;Agra & Berger, 2009). The anxiolytic properties of the Solanaceae family are also well known empirically for long time.…”
Section: Introductionmentioning
confidence: 99%